Change and stability at the World Bank: inclusive practices and neoliberal technocratic rationality. - Sondarjee, Maïka (Third World Quarterly, 2021)
Arguing that international development policymaking is technocratic is not new. However, examining technocracy as a political rationality sheds new light on intentionality, on the evolution of policymaking practices, and on change and stability as part of a single process. In short, the meaningful adoption of new inclusive practices (change) has stabilised World Bank employees' mode of thought and action (stability). My overall argument is that World Bank employees translate potentially radical new knowledge, tools and concepts through a neoliberal technocratic rationality, thereby translating radical practices into technocratic ones. The concept of translation can further our understanding of how inclusion has reinforced rather than challenged the status quo. I thus consider both stability and change at the World Bank from 1980 to 2010, without downgrading either. This article also explores the spread of this political rationality to borrowing governments and populations through self-censorship and mirroring mechanisms, rendering old fashioned conditionalities obsolete. This research is based on extensive interview material and archival analysis.